A note on intersection of modalities - Tinchev, Tinko (Ann. Sofia Univ. Fac. Math. and Inf., 1995)
In this paper a variant of the tableaux method for a polymodal language is considered, where some of the modalities are interpreted in the Kripke models as the set theoretic intersection of the interpretations of some of the remaining ones. As a consequence the completeness theorem with respect to the class of finite tree-like frames and decidability are obtained.